Catharacta skua subsp. hamiltoni Hagen 1952 - Johannessen, Lars Erik; Lifjeld, Jan T. (Zenodo, 2022)
Catharacta skua hamiltoni Hagen, 1952 Birds of Tristan da Cunha. Results of the Norwegian scientific expedition to Tristan da Cunha 1937–1938, No. 20: 135–145. Current name: Stercorarius antarcticus hamiltoni (Hagen, 1952) Syntype NHMO-BI-67601 [I026282]; Study skin; Imm. F; Yngvar Hagen (80), 31 January 1938; SHN 2: Nightingale; 37.427° S, 12.478° W; 13a. Syntype NHMO-BI-67602 [I026283]; Study skin; Ad. M; Yngvar Hagen (260), 26 February 1938; SHN: Inaccessible; 37.300° S 12.673° W; 13b. Syntype NHMO-BI-67603 [I026284]; Study skin; Juv. F; Yngvar Hagen (57), 20 January 1938; SHN: Inaccessible; 37.300° S 12.673° W; 13c. Syntype NHMO-BI-67604 [I026285]; Study skin; Ad. M; Yngvar Hagen (3), 16 December 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 14a. Syntype NHMO-BI-67605 [I026286]; Study skin; Ad. F; Yngvar Hagen (75), 25 January 1938; SHN: Tristan da Cunha; 37.105° S 12.278° W; 14b. Syntype NHMO-BI-85384; Study skin; Ad. F; Yngvar Hagen (2), 16 December 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 14c. Syntype NHMO-BI-92659; Blown eggshell; Egg; Yngvar Hagen (352), 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 5a. Syntype NHMO-BI-92660; Blown eggshell; Egg; Yngvar Hagen (356), 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 5b. Syntype NHMO-BI-92661; Blown eggshell; Egg; Yngvar Hagen (353), 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 5c. Syntype NHMO-BI-92662; Blown eggshell; Egg; Yngvar Hagen (357), 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 5d. Syntype NHMO-BI-92663; Blown eggshell; Egg; Yngvar Hagen (358), 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 5e. Syntype NHMO-BI-92664; Blown eggshell; Egg; Yngvar Hagen (355), 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 5f. Syntype NHMO-BI-92665; Blown eggshell; Egg; Yngvar Hagen (354), 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 5g. Syntype NHMO-BI-92666; Blown eggshell; Egg; Yngvar Hagen (351), 1937; SHN: Tristan da Cunha; 37.105° S 12.278° W; 5h. Syntype NHMO-BI-92668; Blown eggshell; Egg; Yngvar Hagen (350), 1937; SHN: ...